Use of English masterclass basic English Grammar for advanced learners (phrasal verbs & collocations) - Roche, Marc (Basic English Grammar for Use of English Series, 2019)
English grammar is incredibly important if you want to communicate fluently in English. Improving your grammar and vocabulary for Use of English, will not only help you achieve the results you want, but it will also improve your confidence and social skills in English. "Use of English Masterclass: Basic English Grammar for Advanced Learners (Phrasal Verbs & Collocations)", is a relatively short book packed full of grammar and vocabulary exercises and explanations to help you perfect your use of English. This grammar book focuses on phrasal verbs and collocations, and is ideal for anyone who has problems understanding, remembering and using English vocabulary and grammar.